Pendampingan Legalitas Usaha Dan Penguatan Profie Digital Bagi UMKM Kota Cirebon - Ahmad Rifai; Nana Suarna; Difa Aulia Farradila; Muhammad Zeya Sebastian (CV. Multi Kreasi Media, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic development; however, many still face challenges related to business legality and digital business identity. These limitations restrict their access to government assistance programs, financing opportunities, business partnerships, and broader market promotion. This community service program aimed to enhance the capacity of MSMEs through business legality assistance and digital business profile development for five MSMEs in Cirebon City, namely Warung Kopi/Angkringan, Wonton, Orenz Drink, Noenk Ice, and Afiqah Banana. The program employed a participatory approach consisting of needs assessment, business legality education, assistance in obtaining the Business Identification Number (Nomor Induk Berusaha/NIB), digital business profile development, implementation support, and monitoring and evaluation. The results demonstrated that all participating MSMEs improved their understanding of the importance of business legality, organized their business administration more systematically, and developed comprehensive digital business profiles containing business identity, product information, visual documentation, contact details, and communication channels. Furthermore, the assistance enhanced participants' ability to utilize digital business profiles as effective information and promotional media, thereby strengthening their business identity and increasing consumer accessibility. The integrated mentoring model successfully combined administrative strengthening with digital transformation within a systematic empowerment framework. This program contributes to improving MSMEs' capacity to establish better business governance, enhance consumer trust, and strengthen the competitiveness of local products in a sustainable manner.